Small groups as complex systems formation, coordination, development, and adaptation - Arrow, Holly; McGrath, Joseph Edward, 1927-; Berdahl, Jennifer L.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
This general theory of small groups as complex systems draws on general systems theory, dynamical systems theory, and complexity and chaos theory in offering a more complete understanding of the nature of group behaviour and the factors which shape it.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Small groups; Teams in the workplace; Electronic books